The Italian version of the Thinking About Life Experiences Questionnaire and its relationship with gender, age, and life events on Facebook. Issue 2 (23rd January 2020) - Caci, Barbara; Scrima, Fabrizio; Cardaci, Maurizio; Miceli, Silvana
Summary: The present study provided a cross‐cultural validation of the Thinking About Life Experiences Scale‐revised (TALE‐R) in an Italian sample of Facebook users ( n = 492; female = 378; male = 114; mean age 26.1) to test for replication and universality of the TALE‐R three‐factor model. Furthermore, it explored the interrelations among gender, age, the scores at the TALE‐R and the frequency of posting textual/visual information about individuals' life events on Facebook. Results at exploratory and confirmatory factor analysis gave empirical support to both of a tripartite model for the functions of autobiographical memory (i.e., directive‐behavior, social‐bonding, and self‐continuity) and measurement invariance of this three‐factor model across gender and age. Further results at linear correlation and regression analyses showed that directive‐behavior and self‐continuity functions of autobiographical memory are significantly related to the ways people use Facebook for personal documentation. Age differences more than gender influence this association. Discussion and conclusion reported both theoretical and empirical implications of the findings of the study.